Synthesis, structures, and reactivity of isomers of [RuCp*(1, 4-(Me2N)2C6H4)]2. Issue 37 (25th August 2021) - Longhi, Elena; Risko, Chad; Bacsa, John; Khrustalev, Victor; Rigin, Sergei; Moudgil, Karttikay; Timofeeva, Tatiana V.; Marder, Seth R.; Barlow, Stephen
Abstract : [RuCp*(1, 4-(Me2 N)2 C6 H4 )]2 is formed as mixture of stereoisomers with very different properties. One has the usual " exo, exo " structure and is air sensitive, while the unprecedented " exo, endo " isomers are more air-stable, yet stronger reductants. Abstract : [RuCp*(1, 3, 5-R3 C6 H3 )]2 Cp* = η 5 -pentamethylcyclopentadienyl, R = Me, Et have previously been found to be moderately air stable, yet highly reducing, with estimated D + /0.5D2 (where D2 and D + represent the dimer and the corresponding monomeric cation, respectively) redox potentials of ca. −2.0 V vs. FeCp2 +/0 . These properties have led to their use as n-dopants for organic semiconductors. Use of arenes substituted with π-electron donors is anticipated to lead to even more strongly reducing dimers. [RuCp*(1-(Me2 N)-3, 5-Me2 C6 H3 )] + PF6 − and [RuCp*(1, 4-(Me2 N)2 C6 H4 )] + PF6 − have been synthesized and electrochemically and crystallographically characterized; both exhibit D + /D potentials slightly more cathodic than [RuCp*(1, 3, 5-R3 C6 H3 )] + . Reduction of [RuCp*(1, 4-(Me2 N)2 C6 H4 )] + PF6 − using silica-supported sodium–potassium alloy leads to a mixture of isomers of [RuCp*(1, 4-(Me2 N)2 C6 H4 )]2, two of which have been crystallographically characterized. One of these isomers has a similar molecular structure to [RuCp*(1, 3, 5-Et3 C6 H3 )]2 ; the central C–C bond is exo, exo, i.e., on the opposite face of both six-membered rings from the metals. A D + /0.5D2 potential of −2.4 V is estimated for this exo, exo dimer, more reducing than that of [RuCp*(1, 3, 5-R3 C6 H3 )]2 (−2.0 V). This isomer reacts much more rapidly with both air and electron acceptors than [RuCp*(1, 3, 5-R3 C6 H3 )]2 due to a much more cathodic D2 ˙ + /D2 potential. The other isomer to be crystallographically characterized, along with a third isomer, are both dimerized in an exo, endo fashion, representing the first examples of such dimers. Density functional theory calculations and reactivity studies indicate that the central bonds of these two isomers are weaker than those of the exo, exo isomer, or of [RuCp*(1, 3, 5-R3 C6 H3 )]2, leading to estimated D + /0.5D2 potentials of −2.5 and −2.6 V vs. FeCp2 +/0 . At the same time the D2 ˙ + /D2 potentials for the exo, endo dimers are anodically shifted relative to those of [RuCp*(1, 3, 5-R3 C6 H3 )]2, resulting in much greater air stability than for the exo, exo isomer.